Graphic Novels as Tools for Teaching Complexity About Israel. Issue 3 (3rd July 2019) - Reingold, Matt
ABSTRACT: Building on the established idea that to provide students with a full portrait of Israeli society and history, educators must introduce greater complexity into their Israel curriculum, the following paper explores three recently published graphic novels about Israel and considers how each offers opportunities for considering Israel in more nuanced ways. The paper is grounded in recent research about Israel education and empirical studies about graphic novels in education. Each of the three texts highlights aspects of Israeli society that are less frequently addressed in curriculum about Israel and therefore provide opportunities for presenting students with primary sources that directly grapple with the complexities of Israeli society.